Impact of Botulinum Toxin Injections on Quality of Life of Patients with Long-Standing Peripheral Facial Palsy - Jérémy Amar; Frédéric Tankere; Diane Picard; Lauranne Alciato; Fabienne Carré; Claire Foirest (Toxins, 2024)
(1) Background: Sequels of facial palsy lead to major psychosocial repercussions, disrupting patients’ quality of life (QoL). Botulinum toxin (BoNT) injections can permit us to treat long-standing facial palsy, improving facial symmetry and functional signs including synkinesis and contractures. (2) Methods: The main aim of this study was to assess the evolution of the QoL for patients with long-standing facial palsy before, at 1 month, and at 4 months after BoNT injections by using three questionnaires (HFS-30, FaCE, and HAD). The other goals were to find clinical factors associated with the improvement in the QoL and to assess the HFS-30 questionnaire for patients with unilateral facial palsy (3) Results: Eighty-eight patients were included in this study. There was a statistically significant improvement in QoL at 1 month after injections, assessed using the three questionnaires. This improvement was sustained at 4 months after the injections, with a statistically significant difference for the HFS-30 and FaCE questionnaires. (4) Conclusions: This study showed that the BoNT injections lead to a significant increase in the QoL of patients with unilateral facial palsy. This improvement is sustained 4 months after the injections.